1989
DOI: 10.1111/j.1532-5415.1989.tb01571.x
|View full text |Cite
|
Sign up to set email alerts
|

Tying Down the Elderly

Abstract: The apparently widespread practice of physical restraint of the elderly has received little systematic research, despite reported clinical awareness of its iatrogenic effects on frail elders. Prevalence rates in various settings range between 6% and 86%, with cognitive impairment an important risk factor for restraint. Despite strongly held beliefs, efficacy of restraints for safeguarding patients from injury has not been demonstrated clinically. This paper reviews the current status of knowledge regarding phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…Until the 1980s, the nursing home industry assumed that physical restraint of persons with dementia was a necessary component of effective care. Within a few short years, researchers and practitioners demonstrated that restraint use had adverse health and psychological consequences, 55,56 attitudes shifted, 57,58 legislation was enacted, 59 and restraint use was markedly reduced 60–62 . This clinical trial supports the growing conviction that a similar shift in attitudes and practice can and should occur regarding bathing and other personal care activities.…”
Section: Discussionmentioning
confidence: 63%
“…Until the 1980s, the nursing home industry assumed that physical restraint of persons with dementia was a necessary component of effective care. Within a few short years, researchers and practitioners demonstrated that restraint use had adverse health and psychological consequences, 55,56 attitudes shifted, 57,58 legislation was enacted, 59 and restraint use was markedly reduced 60–62 . This clinical trial supports the growing conviction that a similar shift in attitudes and practice can and should occur regarding bathing and other personal care activities.…”
Section: Discussionmentioning
confidence: 63%
“…Contractures can be a sign that residents are not receiving appropriate joint exercises and adequate care (Evans and Strumpf 1989). Figure 1 shows that the percent of residents with contractures increased by 44.3 percent (from 15.8 percent to 22.8 percent of all nursing home residents) between 1991 and 1997 (significant at the 0.01 level using a nonparametric Wilcoxon chi-square test).…”
Section: Findings Resident Characteristics and Conditionsmentioning
confidence: 92%
“…Enforced immobility due to restraint use is endemic among the United States elderly compared to the treatment of older persons in most other countries. Restraint use has clearly been demonstrated to cause a variety of health problems in older persons 14 . Many of the invasive high technological investigations undertaken may further increase mortality.…”
Section: Average Life Expectancy At Birth*mentioning
confidence: 99%